Toward paratuberculosis control in animals: current updates and future perspectives - El-Sayed, AA; Kamel, M; Zschoeck, M (Journal of the Hellenic Veterinary Medical Society, 2024)
Paratuberculosis is a chronic non-curable disease, that affects domesticated and wild ruminants, pets and even humans. This disease causes significant economic losses worldwide. Many countries have implemented control programs to eradicate the disease. Such programs face great challenges due to the nature of the pathogen itself, the immune response, the method of pathogen shedding in susceptible animals, and the absence of accurate diagnostic tools, efficient vaccines, and curative medication. However, some control programs succeeded in eradicating the disease, others were less effective and achieved less success. The present review discusses the elements required in disease control protocols and highlights the importance of disease elimination. These control strategies include optimum application of management measures and proper use of combined diagnostic techniques to accurately identify MAP infected animals with high sensitivity and specificity. Nanotechnology has shown promising results in the diagnosis and control of paratuberculosis. All available vaccines do not completely protect the population, but they actually reduce the clinical signs, pathogen shedding and provoke cellular and humoral immune responses. Although the test and slaughter policy of paratuberculosis is considered an effective way for its control, several obstacles hinder its application.